MYSIR 2022 Virtual E-Abstract 1 - Interventional Radiology, Malaysian Society of (The Interventionalist Journal, 2022)
1. ABERRATION IN VARIATION: DECEPTION BY A CTA OCCULT BLEEDING VARIANT 2. ATYPICAL MULTICENTRIC EXTRA COMPARTMENTAL AND METACHRONOUS GIANT CELL TUMOR RECURRENCE 3. A RARE CASE OF PARARENAL MALAKOPLAKIA 4. A CASE OF ERDHEIM CHESTER DISEASE WITH MULTISYSTEM INVOLVEMENT 5. EXTRAOSSEOUS EWING’S SARCOMA INVOLVING VAS DEFERENS: A CASE REPORT